CONFLICTS IN JENNIFER LEE’S MOVIE SCRIPT FROZEN I - Siti Fatima; Muhammad Fatih Suhadi (JOURNAL OF LANGUAGE, 2023)
The research deals with an analysis of conflict in Jennifer Lee's movie script, Frozen I, focusing on two topics, the types of conflict and exposing the causes of the conflict.  The researchers apply the theory of conflict proposed by Sayuti and Whitfield. This study uses the qualitative method, and the data are analyzed descriptively. Based on the research analysis, the researchers find three results. First, the Frozen I movie script by Jennifer Lee illustrates conflicts and their causes. Second, there are two kinds of conflict in this movie script: internal and external conflict. Internal conflict contains character vs self-conflict. It can be seen in Elsa’s inner turmoil over the power she has, in Elsa's struggle to control her power, and in Elsa's struggle to lower her ego and not hurting the people she loves and the people of Arandelle. External conflict contains character vs character and character vs society. Third, the causes of conflict can be seen when Elsa hurts Anna, when Elsa’s parents die, and when Elsa's power is exposed.